Philosophy for beginners - Osborne, Richard (Orient Blackswan, 2007)
Why does philosophy give some people a headache, others a real buzz, and yet others a feeling that it is subversive and dangerous? Why do a lot of people think philosophy is totally irrelevant? What is philosophy anyway?